A comparison of tissue preparation methods for protein extraction of cocoa (Theobroma cacao L.) pod - Ascensión Martínez-Márquez; Jaime Alfredo Morante-Carriel; Roque Bru-Martínez (Acta Agronómica)
Cocoa, Theobroma cacao L. is one of the main tropical industrial crops. Cocoa has a very high level of interfering substances, such as polysaccharides and phenolic compounds that could prevent the isolation of suitable protein. Efficient methods of protein extraction are a priority to successfully apply proteomic analyses. We compared and evaluated two methods (A and B) of tissue preparation for total protein extract by phenol/SDS extraction protocol. The difference in the application of the two methods was that extensively washed dry powder of pod tissue were made in Method A, whereas that crude extract were prepared Method B. Extracted proteins were examined using one-dimensional electrophoresis (1-D). Results show that each extraction method isolated a unique subset of cocoa pod proteome. Principal component analysis showed little variation in the data obtained using Method A, while that in Methods B showed no low reproducibility, thus demonstrating that Method A is a reliable for preparing cocoa pod proteins. The protocol is expected to be applicable to other recalcitrant plant tissues and to be of interest to laboratories involved in plant proteomics analyses. A combination of extraction approaches is recommended for increasing proteome coverage when using gel-based isolation techniques.